Synchrotron based study of As mobility and speciation in tailings from a mining site in Mexico. Issue 1 (February 2017) - Loredo-Portales, R.; Castillo-Michel, H.; Aquilanti, G.; De La Rosa-Álvarez, Ma.G.; Rocha-Amador, D.O.; Vogel-Mikus, K.; Kump, P.; Cruz-Jiménez, G.
Highlights: As concentrations in tailings and soils surpassed the values allowed for Mexico. As levels in the mobile fraction represent a threat for human health. As is present as As V, forming iron arsenates with kankite-like structure. The presence of iron arsenates were confirmed by two μ X-ray techniques. Abstract: Mine Tailings of "La Aurora", a mining site located in central Mexico, display anomalous concentrations of As, Zn, Pb, Cu and Cd. However, data on their potential toxicity is not available. It is known that toxicity is related to elemental speciation. In this work, we evaluated the biogeochemical dynamics of As in terms of mobility and chemical nature. For this purpose, samples of soils, mine tailings, plants and water were collected. Synchrotron based techniques and chemical fractionation extractions were used to determine As speciation, potential mobility, and bioavailability. Our results showed that As is present in concentrations up to 12, 672 ± 34 and 326 ± 10 mg kg −1 in mine tailings and nearby soils, respectively. X-ray Absorption Spectroscopy (XAS) analysis demonstrated that As is present as As V in a structure similar to that of kankite (FeAsO4 ·3.5H2 O) and beudantite (PbFe3 (AsO4 )(SO4 )(OH)6 ). The presence of these mineral structures were confirmed by μ X-Ray Fluorescence and X-ray Absorption Near Edge Structure (μ-XRF/XANES). Arsenic was also detected in plant species growing in the tested soils. The highest As concentrations were determined in the roots of Baccharis salicifolia (up to 44 mg kg −1 ). In a creek nearby the mine tailings, As levels of 163 ± 15 μg L −1 were quantified. In terms of phytoaccessibility and bioaccessibility, As levels can be considered toxic for both plants and humans. According to sequential extraction results, As is associated mainly with the crystalline Fe-Ox fraction.